PENGARUH GAYA GEMPA TERHADAP BANGUNAN RUKO 2 LANTAI MENGGUNAKAN METODE STATIK EKUIVALEN - Irawan, Teddy; Anggrainy, Rita; Agustini, Marice (Universitas Muhammadiyah Palembang, 2024)
Earthquakes are vibrations that occur due to the meeting of continental plates (tectonics). Earthquake planning is carried out to ensure safety in the aspects of strength, serviceability and durability of a building. The loads on the building are divided into fixed loads and environmental loads. This research focuses on structural analysis by comparing the results of the earthquake load analysis that was input into the structure of the 2-story shophouse. As reinforcement is 560-317-181 mm2 top reinforcement and 366-228-360 mm2 bottom reinforcement for buildings without earthquake loads. Meanwhile, the results of As reinforcement are 751-395-241 mm2 for top reinforcement and 410-299-418 mm2 for bottom reinforcement. The increase in As reinforcement occurs due to the earthquake load and the influence of the magnitude of the earthquake load.